Outcome in elderly individuals with moderate and severe head injury: a tertiary centre experience - Rajasekaran, Gurusamy; Venkatesh, Raju (International Journal of Research in Medical Sciences, 2018)
Background: The prognosis of patients with moderate and severe head injuries is poor in elderly individuals which affects not only their families and also the society. An accurate and early prediction of survival and functional outcome becomes essential and important to decide the aggressiveness of treatment after the informed counseling of relatives. The aim of the present study was to assess the impact of the age on the outcome of the elderly individual with moderate and severe head injury and to compare it with the outcome of younger age group. Methods: Authors retrospectively evaluated 250 patients with moderate (GCS 9-13) and severe (GCS 3-8) TBI after categorizing them into group A (above 60 years of age) and group B (20-59 years of age). Age, sex, mode of injury, level of consciousness as in GCS, management and CT findings were assessed for outcome and comparisons were made. Results: The mean age for good outcome in elderly group is 66.8 and for bad outcome is 70.1 years. The mean age for good outcome in younger group is 33.2 and for bad outcome is 47.5 years. Elderly patients fare worse in all factors assessed when compared to younger group. Conclusions: Head injuries in old age associated with poor GCS serves as a basis for making early prediction for the likelihood of poor outcome.